Temporary teacher’s hiring policy in the municipal educational system of Mocajuba-PA - Feldman, Ariel; Correa Martins, Roberta Adriane (Debates em Educação, 2023)
The objective is to analyze the hiring policy for temporary teachers in Mocajuba-PA between 2009 and 2021. An exploratory case study was used in a qualitative approach, employing documental analysis, semi-structured interviews and participant observation as a data collection instrument. The analyzed results indicate that hiring is based on clientelist relationships, with the distribution of positions in exchange for political loyalty. It was also observed that the temporary teachers are not protected by legislation and suffer from repeated salary delays.